FACTORS OF ORGANIZATIONAL CULTURE CHANGE - Kulvinskienė, Violeta Raimonda; Šeimienė, Eleonora Seminogova (Ekonomika, 2009)
Organizational culture has a significant impact on the organization members’ life and in general it helps a company to achieve positive financial results. Organizational culture is very important in achieving internal integration and implementation of the strategy of adaptation in the external environment. Therefore a lot of companies explore their organizational culture and leaders, if needed, seek consciously to form, develop and change organizational culture.The aim of the article is to analyze the theoretical attitudes towards organizational culture change, to present research results of furniture manufacturing company‘s organizational culture, to describe the aspects that had impact on the organizational culture change and the matrix of organizational culture management.The object of the research is factors that have impact on the organizational culture change.Methods of research: analysis and generalization of literature, opinion survey of organization members by means of the designed questionnaire and in-depth interview as well as comparative analysis.Results of the research show that organizational culture change during 2006–2008 can be described as the movement from the “hierarchy” type towards “adhocracy” type and the main factors that had made impact on the organizational culture change were persons from outside incorporated in the organization and the installation of new technology. The main conclusion of the article is that it is important to establish and ensure continuous monitoring of the organizational culture, to estimate factors that have impact on the organizational culture change and to establish the matrix of organizational culture management in order to manage organizational culture in the right direction.